Characterizing the Cultural Spatial Structure of The Pangururan District Context - Hery Samuel Simarmata (International Journal of Architecture and Urbanism, 2021)
An area is basically formed due to geographical conditions and local cultural aspects that influence it. In this Pangururan village, its geographical condition is close to Lake Toba, and the Toba Batak culture is the most abundant culture in this region. The Toba Batak culture generally inhabits around of Lake Toba in North Sumatra, which means it is located between a lake and a mountain so that the average community works as fishermen and farmers. This led to the growth of settlements around the hill area and also on the edge around Lake Toba. This is certainly an aspect that affects the characterizing of the cultural spatial structure of Pangururan district context. The purpose of this study was to get an overview of the Cultural Spatial Structure of Pangururan Regency.